APLIKASI REKAP KEHADIRAN DAN PENJADWALAN UNTUK GURU HONORER SEKOLAH DASAR NEGERI KARTIKA SEJAHTERA 01 BERBASIS WEB - Muhammad Dzaky (2023)
Elementary school is very important because it has a big impact on building the country and the nation and will have a big impact on what we do for the country in the future. SD Negeri Kartika Sejahtera 01 is one of the choices of elementary schools in Bogor district. The attendance and scheduling recap system for honorary teachers at SDN Kartika Sejahtera 01 still uses a manual system. This can be detrimental for honorary teachers because it can result in damage and loss of data. From these problems, a web-based attendance and scheduling information recap information system for honorary teachers at SDN Kartika Sejahtera 01 is needed. In designing the system, researchers used the waterfall method to adjust the needs of the system developed based on the results of observations at the school. The information system is created using Visual Studio Code for coding and using the CodeIgniter 4 framework to assist researchers in creating an attractive display. This system is expected to be the right choice to solve school problems.